Integrated Femtosecond Pulse Amplifier - Gaafar, Mahmoud A.; Ludwig, Markus; Wang, Kai; Wildi, Thibault; Voumard, Thibault; Sinobad, Milan; Lorenzen, Jan; Francis, Henry; Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal; Geiselmann, Michael; et al. (CLEO: Applications and Technology, CLEO: A and T 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We demonstrate for the first-time f emtosecond p ulse a mplification in a CMOS-compatible photonic chip. We report >50-fold amplification of 1 GHz-repetition-rate chirped femtosecond pulses to 800 W of on-chip peak power with 116 fs pulse duration.
CRIS-Team Scopus Importer:2024-10-04